The 20th Annual Prostate Cancer Foundation Scientific Retreat report. Issue 8 (9th April 2014) - Miyahira, Andrea K.; Simons, Jonathan W.; Soule, Howard R.
<x xml:space="preserve">Abstract</x> The 20th Annual Prostate Cancer Foundation (PCF) Scientific Retreat was held from October 24 to 26, 2013, in National Harbor, Maryland. This event is held annually for the purpose of convening a diverse group of leading experimental and clinical researchers from academia, industry, and government to present and discuss critical and emerging topics relevant to prostate cancer (PCa) biology, and the diagnosis, prognosis, and treatment of PCa patients, with a focus on results that will lend to treatments for the most life‐threatening stages of this disease. The themes that were highlighted at this year's event included: (i) mechanisms of PCa initiation and progression: cellular origins, neurons and neuroendocrine PCa, long non‐coding RNAs, epigenetics, tumor cell metabolism, tumor–immune interactions, and novel molecular mechanisms; (ii) advancements in precision medicine strategies and predictive biomarkers of progression, survival, and drug sensitivities, including the analysis of circulating tumor cells and cell‐free tumor DNA—new methods for liquid biopsies; (iii) new treatments including epigenomic therapy and immunotherapy, discovery of new treatment targets, and defining and targeting mechanisms of resistance to androgen‐axis therapeutics; and (iv) new experimental and clinical epidemiology methods and techniques, including PCa population studies using patho‐epidemiology. Prostate 74:811–819, 2014. © 2014 Wiley Periodicals, Inc.